Technical and vocational education and training (TVET) colleges in South Africa: a framework for leading curriculum change - Terblanche, Tercia Elaine (du Plessis) (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017